Кошевой С. В. Моделирование математического метода волновых полей - Кошевой, С. В. (ХНУРЕ, 2019)
The paper developed a method of modeling full wave fields. Considered the wave method of suppressing multiples waves that do not require knowledge of the depth-velocity model environment. Its convergence and stability for arbitrary plane-layered 3D environments. Further consider the theoretical development and experimental validation